Physical, mechanical and thermal properties of novel bamboo/kenaf fiber-reinforced polylactic acid (PLA) hybrid composites - Khan, Abir; Salit @ Sinon, Mohd Sapuan; Zainudin, E.S.; Zuhri, M.Y.M. (Elsevier, 2024)
This study investigates the physical, mechanical, and thermal properties of bamboo (BF) and kenaf (KF) fiber-reinforced polylactic acid (PLA) hybrid composites. Three hybrid (30BF-70KF, 50BF-50KF, and 70BF-30KF) and two non-hybrid (BF-PLA and KF-PLA) composites were developed through twin screw extrusion and compression molding techniques. The physical properties (density, void content, crystallinity via XRD, and chemical interactions via FTIR), mechanical properties (tensile, flexural, compressive, impact, and hardness), and thermal properties (Thermogravimetric analysis-TGA and Differential scanning calorimetry-DSC) were thoroughly analyzed. BF reinforcement reduced the composites’ density to 1.1826 g/cm³, while the inclusion of KF increased it to 1.2479 g/cm³. 50:50 blend of bamboo-kenaf reinforcement achieved the lowest void content of 0.27 %. The XRD patterns revealed heightened crystallinity in the BF-PLA composite. FTIR analysis showed stable functional groups, with O–H absorption bands indicative of cellulosic fibers. The BF-PLA non-hybrid composite exhibited the highest tensile strength at 25.95 MPa and compressive strength at 173.15 MPa, with the 30BF-70KF hybrid composite showing notable impact strength. Fractured morphology by FESEM revealed superior fiber-matrix adhesion for BF-PLA composite. TGA demonstrated a variation in thermal degradation temperatures, with the BF30-KF70 composite showing the highest onset of degradation at 484 °C. DSC analysis indicated a reduction in the glass transition temperature (Tg) across all fiber-reinforced samples and revealed significant adjustments in melting and crystallization temperatures. This research highlights the potential of BF-KF/PLA hybrid composites in the development of eco-friendly plastic furniture and consumer products. © 2024 Elsevier Ltd